2019
DOI: 10.1177/1756284819836205
|View full text |Cite
|
Sign up to set email alerts
|

18F-fludeoxyglucose positron emission tomography for diagnosis of HCC: implications for therapeutic strategy in curative and non-curative approaches

Abstract: Hepatocellular carcinoma (HCC) is a global health issue with increasing incidence and high mortality rate. Depending on the tumor load and extent of underlying liver cirrhosis, aggressive surgical treatment by hepatectomy or liver transplantation (LT) may lead to cure, whereas different modalities of liver-directed locoregional or systemic tumor treatments are currently available for a noncurative approach. Apart from tumor burden and grade of liver dysfunction, assessment of prognostic relevant biological tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 101 publications
(271 reference statements)
0
7
0
Order By: Relevance
“…Among the 11 patients, 3 (27%) had PET-positive HCC at the time of pre-analysis, but 7 (64%) had PET-positive HCC at the time of post-analysis. Considering that the sensitivity of 18 F-FDG-PET/CT for HCC diagnosis was reported to be about 50% or lower [20, 26], on the other hand, there were many cases presented as PET-positive HCC at the time of post-analysis and the number of patients with PET-positive HCC increased during lenvatinib treatment. This result means that the tumoral biological condition might convert aerobiosis to anaerobiosis for survival under the action of lenvatinib, inhibiting angiogenesis to decrease intratumoral arterial blood flow and proliferation of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 11 patients, 3 (27%) had PET-positive HCC at the time of pre-analysis, but 7 (64%) had PET-positive HCC at the time of post-analysis. Considering that the sensitivity of 18 F-FDG-PET/CT for HCC diagnosis was reported to be about 50% or lower [20, 26], on the other hand, there were many cases presented as PET-positive HCC at the time of post-analysis and the number of patients with PET-positive HCC increased during lenvatinib treatment. This result means that the tumoral biological condition might convert aerobiosis to anaerobiosis for survival under the action of lenvatinib, inhibiting angiogenesis to decrease intratumoral arterial blood flow and proliferation of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, tumor size and 18 F-FDG-PET positivity were independent factors related to metastatic recurrence after RFA. Some reports have already indicated that 18 F-FDG-PET has high predictive value as a surrogate for the presence of microvascular invasion [27]. Ochi et al identified SUV max as the only independent predictive factor for microsatellite distance > 1 cm from the primary tumor lesion [28].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy of 18 F-FDG PET in HCC is limited by the difference in enzyme expression between different tumor gradings. In contrast, the enzyme activity in moderately/poorly differentiated HCC compared with non-involved liver regions resulted in an increase in SUV, thus allowing tumor detection ( 11 ). Lee et al found that HCC with a high tumor-to-liver SUV ratio (TLR) expressed higher levels of glucose transporter isoform 1 than HCC with a low TLR; furthermore, the proliferation and migration of HCC cells with high 18 F-FDG uptake reduced after treatment with glucose uptake inhibitors ( 62 ).…”
Section: Methodsmentioning
confidence: 99%